Gleditsia Saponin C Induces A549 Cell Apoptosis via Caspase-Dependent Cascade and Suppresses Tumor Growth on Xenografts Tumor Animal Model - Cheng, Ye; He, Weidong; He, Yongming (Frontiers in Pharmacology, 2018)
Saponins are natural compounds and possess the most promising anti-cancer function. Here, a saponin gleditsia saponin C (GSC), extracted from gleditsiae fructus abnormalis, could induce apoptosis of lung tumor cell line A549 via caspase dependent cascade and this effect could be prevented by the caspase inhibitors. In addition, GSC induced cell death companied with an increase ratio of Bax:Bcl-2 and inhibition of ERK and Akt signaling pathways. Meanwhile, GSC suppressed TNF inducing NF-κB activation and increased the susceptibility of lung cancer cell to TNF induced apoptosis. Furthermore, on mouse xenograft model, GSC significantly suppressed tumor growth and induced cancer cell apoptosis, which validated the anti-tumor effect of GSC. Based on these results, GSC might be a promising drug candidate of anti-lung cancer for its potential clinical applications.